If in the expansion of ${\left( {1 + x} \right)^m}{\left( {1 - x} \right)^n}$ , the coefficients of $x$ and ${x^2}$ are 3 and -6 respectively, then the value of m is:
$A.$ 6
$B.$ 9
$C.$ 12
$D.$ 24
Answer
Verified
122.4k+ views
Hint: Use binomial theorem of series expansion.
Expanding both the terms of the above term we get:
\[
{\left( {1 + x} \right)^m}{\left( {1 - x} \right)^n} \\
= \left( {1 + {}^m{C_1}{x^1} + {}^m{C_2}{x^2} + {}^m{C_3}{x^3} + ........} \right)\left( {1 - {}^n{C_1}{x^1} + {}^n{C_2}{x^2} - {}^n{C_3}{x^3} + ........} \right) \\
= 1\left( {1 + {}^m{C_1}{x^1} + {}^m{C_2}{x^2} + {}^m{C_3}{x^3} + ........} \right) \\
- {}^n{C_1}{x^1}\left( {1 + {}^m{C_1}{x^1} + {}^m{C_2}{x^2} + {}^m{C_3}{x^3} + ........} \right) \\
+ {}^n{C_2}{x^2}\left( {1 + {}^m{C_1}{x^1} + {}^m{C_2}{x^2} + {}^m{C_3}{x^3} + ........} \right) \\
+ \cdots \cdots \cdots \\
\\
\]
Expanding the equation further to find the coefficients, we get:
\[ \Rightarrow 1 + x\left( {{}^m{C_1} - {}^n{C_1}} \right) + {x^2}\left( {{}^m{C_2} - {}^m{C_1}{}^n{C_1} + {}^n{C_2}} \right) + \cdots \cdots \]
Hence, the coefficient of the term containing $x$ is
$
\Rightarrow {}^m{C_1} - {}^n{C_1} = 3 \\
\Rightarrow m - n = 3 \\
$ ---- (1)
Similarly coefficient of the term containing ${x^2}$ is
$
\Rightarrow {}^m{C_2} - {}^m{C_1}{}^n{C_1} + {}^n{C_2} = - 6 \\
\Rightarrow m\left( {m - 1} \right) - 2mn + n\left( {n - 1} \right) = - 12 \\
\Rightarrow {m^2} - m - 2mn + {n^2} - n = - 12 \\
\Rightarrow {\left( {m - n} \right)^2} - \left( {m + n} \right) = - 12 \\
\Rightarrow 9 - \left( {m + n} \right) = - 12 \\
\Rightarrow m + n = 21 \\
$ ---- (2)
Adding equation 1 and 2 to find the value of m
$
\Rightarrow \left( {m + n} \right) + \left( {m - n} \right) = 21 + 3 \\
\Rightarrow 2m = 24 \\
\Rightarrow m = 12 \\
$
Hence option C is the correct answer.
Note: - In the above question binomial theorem of series expansion has been used in the very first step to expand the terms. We do not need to expand and multiply the whole series as we were concerned with only the first and second power of x so only two to three terms have been considered.
Expanding both the terms of the above term we get:
\[
{\left( {1 + x} \right)^m}{\left( {1 - x} \right)^n} \\
= \left( {1 + {}^m{C_1}{x^1} + {}^m{C_2}{x^2} + {}^m{C_3}{x^3} + ........} \right)\left( {1 - {}^n{C_1}{x^1} + {}^n{C_2}{x^2} - {}^n{C_3}{x^3} + ........} \right) \\
= 1\left( {1 + {}^m{C_1}{x^1} + {}^m{C_2}{x^2} + {}^m{C_3}{x^3} + ........} \right) \\
- {}^n{C_1}{x^1}\left( {1 + {}^m{C_1}{x^1} + {}^m{C_2}{x^2} + {}^m{C_3}{x^3} + ........} \right) \\
+ {}^n{C_2}{x^2}\left( {1 + {}^m{C_1}{x^1} + {}^m{C_2}{x^2} + {}^m{C_3}{x^3} + ........} \right) \\
+ \cdots \cdots \cdots \\
\\
\]
Expanding the equation further to find the coefficients, we get:
\[ \Rightarrow 1 + x\left( {{}^m{C_1} - {}^n{C_1}} \right) + {x^2}\left( {{}^m{C_2} - {}^m{C_1}{}^n{C_1} + {}^n{C_2}} \right) + \cdots \cdots \]
Hence, the coefficient of the term containing $x$ is
$
\Rightarrow {}^m{C_1} - {}^n{C_1} = 3 \\
\Rightarrow m - n = 3 \\
$ ---- (1)
Similarly coefficient of the term containing ${x^2}$ is
$
\Rightarrow {}^m{C_2} - {}^m{C_1}{}^n{C_1} + {}^n{C_2} = - 6 \\
\Rightarrow m\left( {m - 1} \right) - 2mn + n\left( {n - 1} \right) = - 12 \\
\Rightarrow {m^2} - m - 2mn + {n^2} - n = - 12 \\
\Rightarrow {\left( {m - n} \right)^2} - \left( {m + n} \right) = - 12 \\
\Rightarrow 9 - \left( {m + n} \right) = - 12 \\
\Rightarrow m + n = 21 \\
$ ---- (2)
Adding equation 1 and 2 to find the value of m
$
\Rightarrow \left( {m + n} \right) + \left( {m - n} \right) = 21 + 3 \\
\Rightarrow 2m = 24 \\
\Rightarrow m = 12 \\
$
Hence option C is the correct answer.
Note: - In the above question binomial theorem of series expansion has been used in the very first step to expand the terms. We do not need to expand and multiply the whole series as we were concerned with only the first and second power of x so only two to three terms have been considered.
Recently Updated Pages
The real roots of the equation x23 + x13 2 0 are A class 11 maths JEE_Main
Find the reminder when 798 is divided by 5 class 11 maths JEE_Main
Let A and B be two sets containing 2 elements and 4 class 11 maths JEE_Main
A ray of light moving parallel to the xaxis gets reflected class 11 maths JEE_Main
A man on the top of a vertical observation tower o-class-11-maths-JEE_Main
If there are 25 railway stations on a railway line class 11 maths JEE_Main
Trending doubts
JEE Main 2025 Session 2: Application Form (Out), Exam Dates (Released), Eligibility & More
JEE Main Login 2045: Step-by-Step Instructions and Details
JEE Main Chemistry Question Paper with Answer Keys and Solutions
JEE Main Exam Marking Scheme: Detailed Breakdown of Marks and Negative Marking
JEE Main 2023 January 24 Shift 2 Question Paper with Answer Keys & Solutions
JEE Main Chemistry Exam Pattern 2025
Other Pages
JEE Advanced Marks vs Ranks 2025: Understanding Category-wise Qualifying Marks and Previous Year Cut-offs
NCERT Solutions for Class 11 Maths Chapter 9 Straight Lines
NCERT Solutions for Class 11 Maths Chapter 12 Limits and Derivatives
NCERT Solutions for Class 11 Maths Chapter 8 Sequences and Series
NCERT Solutions for Class 11 Maths Chapter 10 Conic Sections
NCERT Solutions for Class 11 Maths Chapter 13 Statistics